An Assessment of Urban Canopy Cover Over Chiang Mai Municipality - Ongprasert, Preecha (วารสารวนศาสตร์ไทย, 2022)
Total canopy cover and canopy cover over Chiang Mai City Municipality (CMCM) was made based on the results of aerial photography interpretation. Canopy cover of the city varied between 21.5% and 33.9% by subdistrict, averaging 31.1% citywide. The interpretation of urban tree canopy cover distribution from aerial photographs has provided a geographical baseline for understanding the current situation, including future planning and management of the urban forest of the city. Meanwhile, there were potential patch of natural vegetation located within Chiang Mai University where is covered with remnant of original vegetation of mixdeciduous and dry evergreen forests. That area contains significant potential for developing to be large green space close to the city centre. Key words: canopy cover, urban forest, aerial photogragraph interpretation, Chiang Mai